2018
DOI: 10.3390/ma11040605
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma (PC12) Cell Response on Mechanobactericidal Titanium Surfaces

Abstract: Titanium is a biocompatible material that is frequently used for making implantable medical devices. Nanoengineering of the surface is the common method for increasing material biocompatibility, and while the nanostructured materials are well-known to represent attractive substrata for eukaryotic cells, very little information has been documented about the interaction between mammalian cells and bactericidal nanostructured surfaces. In this study, we investigated the effect of bactericidal titanium nanostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…PC 12 cells can respond to nerve growth factor (NGF) in serum free or low serum medium by extending neurites and ceasing multiplication [35,36,37]. The effect of THz radiation exposure on PC 12 cell differentiation was further investigated by treating the PC 12 cells with NGF and monitoring the neurite outgrowth for up to 7 days (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…PC 12 cells can respond to nerve growth factor (NGF) in serum free or low serum medium by extending neurites and ceasing multiplication [35,36,37]. The effect of THz radiation exposure on PC 12 cell differentiation was further investigated by treating the PC 12 cells with NGF and monitoring the neurite outgrowth for up to 7 days (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Rat pheochromocytoma PC12 neuronal cell lines are the most used to study the ability of new biomaterials to promote neuronal adhesion and neurite outgrowth (Klymov et al, 2015; Li et al, 2015). Wandiyanto et al (2018) have recently shown that PC12 cells grown on anti-bactericidal titanium nanostructures displayed enhanced proliferation, differentiation and neurite outgrowth compared to non-nanostructured surfaces. Tasnim et al (2018) recently investigated, using the SH-SY5Y cell line, the biocompatibility of graphene oxide coating for commercially available 316 stainless steel.…”
Section: Experimental Models To Study Foreign Body Response To Neuralmentioning
confidence: 99%
“…Environmental factors affecting the growth of animal cells include, among others, optimal medium selection, the temperature of incubation as well as suitable plastic multi-well plates used in experiments, finishing with surface modification of cell culture plates [27][28][29][30]. The appropriate coating helps to overcome the problem of poor cell adhesion to culture vessels [31]. Various surface coating protocols have been developed to skip this technical limitation in designing experiments [32].…”
Section: Introductionmentioning
confidence: 99%